SOCIAL PROBLEMS AS REFLECTED IN THE PREMAN, ANTHOLOGY OF THE SHORT STORY BY TIWIEK SA - Galih Dwi Purboasri; Kundharu Saddhono; Suyitno Suyitno (Center of Language and Cultural Studies [CLCS], 2017)
This study analyzed social problems as reflected in the Preman, an anthology of short story by Tiwiek SA. The social problems were encountered in the attitudes the characters of the stories occured. The study used ontent analysis that use psycholinguistics as an analysis of a literary work. Sources of the study was an anthology consisting of six short stories. The study revealed that social conflict in the story reflected problems in social daily live where Javanese community normally faced. The problems include: thuggery, clashes, greedines, infidelity, prostitution, economy, and social inequality. Themes of good and bad conducts also appeared as performed by the primary characters.